(untitled) (Studia austriaca, 2014)
In spite of its title, the main viewpoint in Horváth’s well-known novel Jugend ohne Gott (1937, Youth without God) belongs to the figure of the teacher, who struggles with God and with his own conscience. This essay raises some apparently unorthodox questions, which might, however, open the way for new interpretations of the novel.